Effects of dietary D-lactate levels on rumen fermentation, microflora and metabolomics of beef cattle - Gao, Qian; He, Jianfu; Wang, Jin; Yan, Yonghui; Liu, Lei; Wang, Zuo; Shen, Weijun; Wan, Fachun (Frontiers in Microbiology, 2024)
Excessive intake of lactate caused by improper use of silage in animal husbandry has adverse effects on rumen fermentation, such as rumen acidosis. The speed of absorption and metabolism of D-lactate in rumen epithelial cells was slower than that of L-lactate, making D-lactate more prone to accumulate and induce rumen acidosis. Therefore, this study was dietary D-lactate into volatile fatty acids increased the energy supply of beef cattle. However, it also increased the ruminal CH4 emissions and the relative abundance of opportunistic pathogen Escherichia-Shigella in beef cattle.